Economic Development in Demographically Shrinking Regions. Challenges and Regional Market Strategies of Firms from Upper Franconia - Matuschewski, Anke; Leick, Birgit (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
Demographic change in terms of decreasing and ageing populations poses a new challenge to regional development and economic prospects in Europe. However, it has been noted that the intensity of demographic shrinking differs widely among the European regions, causing adaptive problems and challenges to varying degrees. Demographic change affects almost every area of economic activity. This article depicts and analyses the associated changes and challenges for regional development in shrinking areas at a micro level. It gives an overview of the extent and intensity of demographic shrinkage for regions as well as its effects on regional development and firms as economic agents in demographically shrinking regions. The overview is based on concepts and theories in economics and economic geography dealing with demographic and economic developments. The main part presents a case study that focuses on changing regional market conditions due to demographic change. Using Upper Franconia as a German case region, we analyse the pressure on local firms and their adaptive strategy-building on regional markets in an exploratory way.